2019
DOI: 10.11648/j.sjph.20190704.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Pediatric Emergency Triage and Its Associated Factors in Wolaita Zone, Ethiopia

Abstract: Background: Most deaths of children in hospital frequently occur within the first 24 hours of admission.Immediate triage on arrival may prevent many of these deaths. Pediatric emergency triage assessment and treatment was introduced in 2014 in Ethiopia, however, there is no evidence which shows its quality and associated factors in the country.Objective:-This study aimed to assess the quality of pediatric emergency triage and its associated factors in selected hospitals of Wolaita zone 2017. Methods: A facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…So, when it comes to emergency unit service, age matters a lot. This finding was in line with those of a different study by Gargamo et al, (2019), which reported that more than a third of participants were between the ages of 20 and 30 years, with a mean age of 30.38+5.2 years. It was also somewhat in line with Sedaghat et al, (2021), who reported that the mean age of subjects in their study was 41 years old.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So, when it comes to emergency unit service, age matters a lot. This finding was in line with those of a different study by Gargamo et al, (2019), which reported that more than a third of participants were between the ages of 20 and 30 years, with a mean age of 30.38+5.2 years. It was also somewhat in line with Sedaghat et al, (2021), who reported that the mean age of subjects in their study was 41 years old.…”
Section: Discussionsupporting
confidence: 92%
“…As it entails evaluating labor conditions and fetal well-being and arranging tests and interventions for obstetric difficulties, obstetric triage is more specialized than general and trauma triage(Rashidiet al 2019 ). Patient dissatisfaction and lengthy wait times are the two most significant problems with obstetric triage (Gargamo et al, (2019). Patients must wait a long time to be examined, which may delay the provision of necessary care and treatment, cause patient dissatisfaction, and increase mortality and morbidity .…”
Section: Discussionmentioning
confidence: 99%
“…with Gargamo et al (2019), who stated. that more than two-thirds of participants were between the ages of 20 and 30 (21) . Concerning gender, it was clear that the majority of nurses were females, this result was matched with Phukubye et al (2021) who stated that more than half of the studied nurses were females (22) .…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...mentioning
confidence: 96%